Combined Methylmalonic Aciduria and Homocystinuria cblC Type of a Taiwanese Infant With c.609G>A and c.567dupT Mutations in the MMACHC Gene - Jenn-Tzong Chang; Ying-Yao Chen; Tze-Tze Liu; Mei-Ying Liu; Pao-Chin Chiu (Pediatrics and Neonatology)
Combined methylmalonic aciduria and homocystinuria, cobalamin (cbl)C type (cblC disease), the most common inborn error of vitamin B12, is a rare disorder of intracellular cbl metabolism because of mutations in the MMACHC gene located in chromosome region 1p34.1. It has become possible to establish phenotype–genotype correlations and to observe ethnicity-related trends. This article provides detailed clinical manifestations and outcomes of a Taiwanese infant boy with early-onset cblC disease, heterozygous for c.609G>A and c.567dupT mutations, although there is limited information about cases with c.609G>A or c.567dupT mutation in the literature. He had no significant clinical abnormality during his neonatal period, whereas elevated C3 level was noted at newborn screening. He presented later with life-threatening manifestations and failure to thrive, which resolved through our treatment, although delayed development was still noted at 6 months of age. To date, all reported cblC patients with the c.609G>A mutation have been East Asians. Therefore, we suggest that c.609G>A should be included in the initial mutation screening tests for a cblC patient in East Asian populations.